Retro-Mode Scanning Laser Ophthalmoscopy Planning for Navigated Macular Laser Photocoagulation in Macular Edema - Boiko, Ernest V. (J Ophthalmol, 2016)
Purpose. To compare treatment areas and navigated macular laser photocoagulation (MLP) plans suggested by retro-mode scanning laser ophthalmoscopy (RM-SLO) image versus optical coherence tomography (OCT) central retinal thickness map and treatment planning among retina specialists. Methods. Thirty-nine eyes with diabetic or branch retinal vein occlusion-related ME undergoing navigated MLP with navigated photocoagulator had OCT and RM-SLO taken. OCT map and RM-SLO image were imported to the photocoagulator and aligned onto the retina. Two retina specialists placed laser spot marks separately based on OCT and RM-SLO images in a random fashion. The spots placed by each physician were compared between OCT and RM-SLO and among physicians. The areas of retinal edema on OCT and RM-SLO of the same eye were also compared. Results. The average number of laser spots using RM-SLO and OCT template was 189.6 ± 77.4 and 136.6 ± 46.8, respectively, P = 0.003. The average area of edema on RM-SLO image was larger than that on OCT map (14.5 ± 3.9 mm(2) versus 10.3 ± 2.8 mm(2), P = 0.005) because of a larger scanning area. There was narrow variability in treatment planning among retina specialists for both RM-SLO (P = 0.13) and OCT (P = 0.19). Conclusion. The RM-SLO image superimposed onto the fundus of the same eye can be used to guide MLP with narrow variability in treatment planning among retina specialists. The treatment areas suggested by RM-SLO-guided MLP plans for ME were shown to be larger than those suggested by OCT-guided plans.